A hopeful heart - Clipston, Amy. (Grand Rapids, Michigan : Zondervan, 2013)
"In A Hopeful Heart, the first novel of the new Hearts of the Lancaster Grand Hotel series from best-selling author Amy Clipston, Hannah finds herself at a crossroads in her life. Her community offers her love and support after the untimely death of her husband, but an Englisher offers her the chance of a new life after her unexpected tragedy. Wealthy businessman Trey Peterson is surprised by his attraction to the gentle Amish woman who works as a housekeeper in the Lancaster Grand Hotel. They share a common bond of loss and are able to offer each other comfort and support as they journey through their grief. Joshua Glick wants nothing more than to offer his friendship and love to Hannah and her family. Not only is he her late husband's brother and business partner, he has always been in love with Hannah. A Hopeful Heart is filled with surprising twists as Hannah tries to balance her life in the Amish community and her growing love for an outsider"--P. [4] of cover.
Keywords: Amish -- Fiction; Widows -- Fiction; Christian fiction